Comprehensive Policy Analysis Of Indonesia's Poverty Alleviation Strategy Through People's School Education - Pardomuan Robinson Sihombing (CV Pena Jaya Pers, 2026)
Purpose: This study analyzes the policy design and strategic implications of the Sekolah Rakyat (People’s School) program under Presidential Instruction Number 8 of 2025 as an instrument to reduce intergenerational poverty through education. Design/methodology/approach: This study employs a qualitative approach using policy analysis, literature review, and comparative analysis of international educational models, including SEED Schools (USA), Escuela Nueva (Colombia), and BRAC (Bangladesh). The analysis is grounded in human capital theory and social reproduction theory. Findings: The findings indicate that Sekolah Rakyat has the potential to improve educational opportunities for students from low-income families through a state-funded boarding school model. However, challenges related to social stigmatization, institutional segregation, fiscal sustainability, and inter-ministerial coordination may affect program effectiveness. Research limitations/implications: This study is limited to secondary data and qualitative analysis. Future studies should examine the long-term educational and socio-economic impacts of the program through empirical research. Practical implications: The study recommends regulatory harmonization, clearer institutional governance, and more inclusive student admission policies to strengthen program implementation and reduce social stigma. Originality/value: This study offers a policy-oriented analysis of Sekolah Rakyat by integrating educational sociology perspectives with international comparative experiences. Paper type: Literature review